The Effect of Poverty Conditions and Educational Facilities on School Participation Levels in Pacitan City - Maharani, Amalia Rizqi; Sishadiyati (Indonesian Journal Publisher, 2025)
Education is a crucial factor in improving the quality of human resources and alleviating poverty. In Pacitan Regency, the hilly geography and limited accessibility affect the distribution of schools and the community's ability to continue their education. This is reflected in the fluctuation of the School Participation Rate (APS) at each level of education, where the APS of elementary school students is relatively stable, while the APS of junior high and senior high schools shows a significant decline, especially among poor families. This study aims to analyze the influence of poverty levels and the number of schools on the APS in Pacitan Regency. The research method used is a quantitative approach with multiple linear regression using secondary time series data from the Central Statistics Agency (BPS). The results show that at the elementary school level, poverty has a positive but insignificant effect, while the number of schools has a negative effect on the APS due to the regrouping policy. At the junior high school level, poverty has a negative effect and the number of schools has a positive effect on the APS. Meanwhile, at the senior high school level, poverty has a significant negative effect, while the number of schools has no significant effect. Overall, economic factors are proven to be more dominant than the availability of schools, especially at the secondary education level.